Production of Bulk Amorphous Steels and Their Characterization - Iqbal, M.; Wang, W. H. (The Nucleus, 2014)
Paramagnetic bulk amorphous steels (BASs) having the compositions Fe50Cr14Mo14C14B6M2 (M = Zr, Nb and Pt) were produced. We have replaced Y, Gd and Dy with Zr, Nb and Pt in the BASs. Materials were characterized by SEM, EDS, DSC and XRD techniques. Density of the as cast Fe50Cr14Mo14C14B6Zr2 was found to be 7.17 g/cm3 which is less than all previously reported BASs. Vicker’s microhardness, nanohardness, elastic modulus and fracture stress are found to be 1240 HV, 14.9 GPa, 248 GPa and 4.96 GPa respectively. Examination of Vicker’s indents show semicircular shear bands around the indents indicating presence of a little ductility in the Fe50Cr14Mo14C14B6Zr2 BAS. This BAS have very promising thermal properties. Melting and liquid temperatures are found to be 1392 and 1543 K respectively which are too high for BASs. Width of supercooled liquid region of 70 K and value of parameter approximately 0.4 indicates very promising thermal stability and high glass-forming ability (GFA). SEM examination of the broken pieces of the compression tests fractured specimens shows parallel and curved shear bands indicating brittleness in the bulk samples. DSC results confirm multistage crystallization. Present investigations on Fe50Cr14Mo14C14B6Zr2 showed that this BAS had better mechanical and thermal properties than many other structural steels.